Evaluation of antimicrobial activity of plant extracts from Brazilian savanna on cariogenic cocci - Bianco, Karina Gerhardt; Gaetti-Jardim, Ellen Cristina; Brighenti, Fernanda Lourenção; Gaetti-Jardim Júnior, Elerson (ARCHIVES OF HEALTH INVESTIGATION, 2017)
This study evaluated the antimicrobial activity of 138 aqueous extracts of 23 plants from Brazilian savanna on cariogenic cocci. Aqueous extracts were prepared from leaves, stems and barks of the plants. The initial screening of antimicrobial activity was performed by the agar diffusion method. Minimal inhibitory concentration (MIC) and minimal bactericidal concentrations were determined using broth dilution method. Time-kill curve were also determined on cells in suspension. The initial screening of antimicrobial activity evidenced that leaves extracts from M. ilicifolius, P. americana, J. cuspidifolia and bark extracts of P. rotundifolia were active on some strains but not all tested microorganisms. Only leaves, bark and stems extracts of M. urundeuva and P. cattleianum were able to inhibit all tested strains. The inhibitory activities of M. urundeuva and P. cattleianum were similar. In general, MBCs were four up to thirty two times higher than MICs. Time-kill curve of the extracts from P. cattleianum and M. urundeuvashowed that a log reduction of the planktonic bacterial inoculum was achieved within 60 minutes of contact. Descriptors: Bacteria; Prevention & Control; Plant Extracts; Dental Caries.